2019
DOI: 10.1007/s00737-019-0951-5
|View full text |Cite
|
Sign up to set email alerts
|

Dispensing patterns of selective serotonin reuptake inhibitors before, during and after pregnancy: a 16-year population-based cohort study from the Netherlands

Abstract: Management of mental illness in the perinatal period with antidepressants is controversial, since evidence emerged on potential harmful effects to the unborn child. However, over time, the dispensing of antidepressants in the perinatal period has increased. We examined perinatal dispensing patterns over time and the role of a recently issued guideline in this regard. We identified a 16year cohort of 153,952 Dutch pregnancies with a delivery date between January 1999 and December 2014. Data included exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 39 publications
7
24
0
Order By: Relevance
“… 30–32 In the Netherlands, approximately 2%–3% of pregnant women use antidepressants. 29 33 34 In the USA, this prevalence is approximately 6%–7%, 35–37 but could even be as high as 15% in some states. 38 Therefore, it is urgent and clinically relevant to investigate alternative approaches to treat antepartum depression, such as bright light therapy (BLT).…”
Section: Introductionmentioning
confidence: 99%
“… 30–32 In the Netherlands, approximately 2%–3% of pregnant women use antidepressants. 29 33 34 In the USA, this prevalence is approximately 6%–7%, 35–37 but could even be as high as 15% in some states. 38 Therefore, it is urgent and clinically relevant to investigate alternative approaches to treat antepartum depression, such as bright light therapy (BLT).…”
Section: Introductionmentioning
confidence: 99%
“…Antidepressant drug use during pregnancy increased from 2.0% of deliveries in 1996 to 7.6% of deliveries in 2004 and 2005 in the United States (Andrade et al, ). Dispensing rates of selective serotonin reuptake inhibitors (SSRIs) steadily increased in Netherland from 0.8% in 1999/2000 to 2.1% in 2013/2014 (Molenaar et al, ). In Denmark, the rate of AD exposure during pregnancy increased from 0.2% in 1997 to 3.2% in 2010 (Jimenez‐Solem et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of depression during pregnancy is substantial (Bennett, Einarson, Taddio, Koren, & Einarson, 2004;Gavin et al, 2005), and use of antidepressants (ADs) during pregnancy has increased in most developed countries in recent decades (Andrade et al, 2008;Jimenez-Solem et al, 2013;Molenaar, Lambregtse-van den Berg, & Bonsel, 2019). Antidepressant drug use during pregnancy increased from 2.0% of deliveries in 1996 to 7.6% of deliveries in 2004 and 2005 in the United States (Andrade et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study suggested that although psychotherapy has been the first treatment option for mild to moderate psychiatric disorder, %70 of patients are primarily treated with antidepressants [3]. The studies also revealed an increase in the prevalence of antidepressant exposure from 0.2% to 3.2% between 1997 and 2010 in Denmark [4] and from 0.8% to 2.1% between 1999 and 2014 in the Netherlands [5]. The rate of use of SSRI (Serotonine Reuptake Inhibitors) in all antidepressants during pregnancy was reported as 63% to 85% [6].…”
Section: Introductionmentioning
confidence: 99%